Manipulating electronic band of NiO/NiMoO4–x nanosheets as robust bifunctional catalyst for water splitting - Qiyu Liu; Jintao Zhang; Jinjun He; Peng Zhang; Zujin Yang; Xihong Lu (Next Nanotechnology)
Due to the issues of energy shortage and environmental pollution, it is crucial to explore environmentally friendly and efficient bifunctional catalysts for oxygen and hydrogen evolution reaction (OER/HER). Herein, we demonstrate an oxygen vacancy-rich NiO/NiMoO4 heterojunction as bifunctional catalyst for electrocatalytic water splitting (denoted as NiO/NiMoO4–x) on commercial nickel foam by a facile hydrothermal-calcination method. The experimental results and density functional theory calculations confirm that the constructed heterostructure and oxygen vacancies optimize the electronic band structure of NiO/NiMoO4–x with more electronic states near the Fermi level, which not only enhances its conductivity, but also promotes exposure of the active sites. Based on this, NiO/NiMoO4–x possesses an impressive OER overpotential of 332 mV and HER overpotential of 34 mV at 10 mA cm–2, simultaneously, a satisfactory stability after continuous operation for 165 h. This work affords valuable insights into the development of durable and inexpensive bifunctional catalysts for electrocatalytic water splitting.